New directions for the protection of food security in Lusophone Africa? Technical cooperation between Brazil and Angola - Silva de Freitas, Jeane (2020)
This article discusses aspects of Brazilian technical cooperation in the field of food security for Portuguese-speaking countries, focusing on or fighting hunger in the Republic of Angola. It examines the process of formation of political andeconomic relations between these countries, the food security strategies adopted by them, and the projects/programs implemented by Angola, based on technical cooperation with Brazil.The premise is that despite the positive progress made in cooperation between the two countries in promoting food security, the phenomenon of hunger is still a persistent problem in the Angolan territory, the result especially of the country’s socioeconomic and institutional conditions.